Gas micro-turbines with high-speed electric generators for local smart energy systems - Kolpakhchyan, Pavel G.; Shaikhiev, Alexander R.; Yatsenko, Elena A.; Goltsman, Boris M.; Oshchepkov, Andrey S. (Nexo Revista Científica, 2020)
At present, the share of energy collected from renewable resources and low-power units is growing, and the generation becomes distributed, having many facilities that operate in co-generation mode. That is why the construction of an energy system with distributed heterogeneous sources and the improvement of its efficiency have become widely discussed issues. This paper proposes a solution of a local smart energy systemfortheTechnoEcoPark, a sciencepark of Rostov State Transport University, Rostov, Russia. The solution aims to integrate the distributed generation facilities, including environmentally friendly renewable resources, grid infrastructure and consumers with controllable and uncontrollable load. Theapproachtothe problem is the application of a smart control systemthatmanagesgeneration, distribution and consumptionof energy in a mini-CHP-based autonomous energy system. Such smart control systems reveal the trends of optimal energydistribution in a autonomousenergysystem. The study substantiates that installation of an in-house mini-CHP can solve the task of supplying heat and powertotheTechnoEcoPark. The important advantage of the solution is a significant reduction of expenses on energy consumption as the generation costs less compared to the grid tariffs. The proposed energy supply system of the TechnoEcoPark exemplifies the integration of heterogeneous heat and power sources and consumers into a commonnetwork. The paper outlines the mechanisms of the energy system efficiency improvement. These mechanisms make it possible to provide heat and power supply services to consumers and to return the generated power into the centralized grid. The materials of the paper can be of use to the specialists and researchers who are interested in generation and distribution of energy in autonomous systems.